Teoria da burocracia: - Freire, Diego Alves (Universidade Federal do Tocantins, 2022)
This paper aimed to analyze the points of approximation of the theory of bureaucracy existing in the organizational reality of the company Believe Tocantins. To achieve this goal, the theoretical matrix approached aspects such as bureaucracy foundation, its characteristics, dysfunctions and advantages. The research was exploratory through a questionnaire with semi-structured questions, and of a qualitative nature. The data analysis shows that after applying the questionnaire, it was found that of ten characteristics listed, seven of them are present in the reality of the organization presented which portrays how much the bureaucracy, although much criticized, is still essential in the life of organizations, as in the case of the company studied here, where only two dysfunctions were not evidenced in the company, which means that the company has dealt well with the bureaucracy and suffered little with its unthinkable effects. In this respect, it can be said that the bureaucracy is present and fulfills a determining role in the company Believe Tocantins.